Acute Pancreatitis in Jordanian Children: A Single Center Experience - Al Droubi, Belal; Altamimi, Eyad (Frontiers in Pediatrics, 2022)
Pediatric pancreatitis is a disease that requires a deeper understanding and further development. Especially in young children, as their etiology, clinical presentation, and disease outcome vary significantly from pancreatitis in adults. The incidence of pancreatitis is increasing, and it is not as rare in children compared to what was previously thought, and might carry significant morbidity and mortality when severe. In this retrospective study from a tertiary care hospital in Jordan, we present a cohort of children with sixty-four episodes of acute pancreatitis. While abdominal pain was the most common presentation in our cohort (97%), classical radiation to the back and relieved with leaning forward was seen in only one third of our patients. Compared to serum amylase, lipase provided superior sensitivity in detecting pancreatitis (98% vs 75%). Abdominal ultrasound is a non-invasive, widely available modality of imaging, using which almost 60% of patients showed an enlarged pancreas. Abdominal ultrasound is however often limited by excessive bowel gas. Anatomical abnormalities were the most common etiology (29%), followed by idiopathic pancreatitis (21%) and biliary causes (21%). Nearly half of patients (54%) had recurrence of one or more episodes of acute pancreatitis later on. Serum Lipase performed better as a diagnostic tool than serum Amylase in our cohort. Congenital biliary-pancreatic abnormality was the most common cause of acute pancreatitis in our cohort. Almost half the patients developed recurrent acute pancreatitis. The rate of pancreatic pseudocyst was (16.7%), and half of them required intervention.